The relationship between low energy availability, injuries, and bone health in recreational female athletes - Gimunová, Marta; Bozděch, Michal; Bernaciková, Martina; Fernandes, Romulo [UNESP]; Kumstát, Michal; Paludo, Ana (PeerJ, 2024)
Background: Low energy availability (LEA) causes pathophysiology of the female athlete’s body affecting the bone and reproductive health and was observed to have a high prevalence in recreational female athletes previously. The aim of this study was to analyse the relationship between low energy availability in females questionnaire (LEAF-Q), bone mineral density (BMD), and postural stability in recreational athletes. Methods: Recreational female athletes (n = 24, age: 23.71 ± 2.94, Tier I) completed LEAF-Q, postural stability measurement during quiet stance (Zebris platform FDM; GmbH) and their BMD was measured using DXA (Hologic QDR Horizon A). Non-parametric statistical tests were used to analyse the relationships between LEAF-Q, BMD, and postural stability and to compare differences between participants divided by the LEAF-Q score and its subscales. Results: Risk of LEA was observed in 50% of recreational athletes participating in this study. Up to 46% of participants perceived menstrual bleeding changes related to training and 37.50% experienced menstrual dysfunction. Body composition and body weight fluctuations were observed to affect postural stability and BMD. With the risk score for LEA, the BMD and postural stability were not negatively affected in recreational athletes. However, the high number of recreational athletes in the risk score for LEA and menstrual dysfunctions highlights the need for public health programs aimed to increase awareness of LEA and its health consequences and for open communication about the menstrual cycle. Future longitudinal studies observing LEA, BMD, menstrual function, postural stability, and their interrelationship in female athletes are needed to increase the knowledge of this topic.
Keywords: Bone mineral density; Centre of pressure; LEAF-Q; Menstrual cycle; Women